Effects of reducing long-term groundwater overdraft in uluova micro-basin - Sekerci, Kursat; Tuna, M. Cihat; Dogan, M. Sahin (Springer Heidelberg, 2025)
Recently, groundwater use has increased significantly in response to limited surface water availability in arid and semi-arid regions. This trend has led to increasing concerns about declining groundwater levels and the risk of overdraft. For the above reasons, a hydroeconomic model was developed in this study to evaluate various management scenarios aimed at mitigating the negative impacts of groundwater overdraft. The Uluhem hydroeconomic model focuses on a total of six different water management operations with different physical constraints. The first scenario is a baseline water operation with groundwater pumping (with overdraft), while the next four scenarios cover four different water management operations where groundwater pumping is restricted at different rates (without overdraft). The sixth and final scenario investigates the installation of a solar-powered system to pump water from a nearby surface water reservoir. This last scenario seeks a potential solution to completely eliminate the agricultural water scarcity and associated scarcity costs arising from the first five scenarios. With the Uluhem model, the water deliveries, water scarcity and economic impacts of these six different management scenarios are analyzed. The findings show that the four different scenarios in which groundwater pumping is restricted contribute positively to the groundwater reservoir but increase water scarcity. The solar power plant installation scenario, on the other hand, offers a promising and sustainable solution that not only effectively addresses water scarcity but also eliminates the associated costs. The study investigates the factors contributing to groundwater overdraft and seeks a sustainable solution to current groundwater utilization. The results emphasize the urgent need for effective and sustainable water management strategies to prevent groundwater overdraft. Overall, the study provides valuable insights into groundwater overdraft problems in the Uluova micro-basin and emphasizes the importance of adopting long-term, sustainable groundwater management practices.
Keywords: Uluova basin; Hydroeconomic model; Overdraft; Water resources management